CORPORATE REPORTING IN COMPARISON OF FINANCIAL PERFORMANCE OF PT MAYORA INDAH TBK AND PT SIANTAR TOP TBK AS AN ALTERNATIVE INVESTMENT - Riska Melati; Anita Munir (Journal of Management and Leadership, 2020)
The purpose of study is to determine the health of the company by comparing which companies are more attractive to invest. This study uses 2 samples of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. The data analysis technique used is a fundamental analysis consisting of five ratios namely; liquidity ratios, solvency, activity, profitability, market value, and sensitivity analysis. The results showed in 2014 to 2018 that the highest liquidity ratio was PT Mayora Indah Tbk. The best solvency ratio is PT Siantar Top Tbk. The highest activity ratio is PT Siantar Top Tbk. The highest profitability ratio is PT Mayora Indah Tbk. The highest market value ratio is PT Siantar Top Tbk. And a sensitivity analysis of Net Present Value (NPV) proves that these two companies are worth investing. As a result, PT Siantar Top is more attractive to invest because is more efficient, healthy and has a low market value with high company value.